Comparative analysis of existing standards and methodologies for interpreting DGA results - Shutenko, O. V.; Kulyk, O. S.; Ponomarenko, S. G. (Typography Madrid, 2021)
The study guide is intended for performing individual computational tasks in the course "Mathematical Bases of Technical Diagnostics". The guide contains a systematised analysis of methods and criteria used to recognise the type of defects in oil-filled equipment based on the results of analysis of gases dissolved in oil. The contents of the problem, an example of its performance and variants for calculation are given. It is intended for full-time and extramural international Masters and learners in English of specialisation No. 141 "Electric power engineering, electrical engineering and electromechanics" with specialisation in "Electrical systems and networks", as well as for applicants, postgraduate students and researchers working in the field of diagnostics of high-voltage electric power equipment state.
Keywords: study guide; thermal defects; radar charts method; MSS method; Key Gas method; IEC 60599 standard